Mitochondrial Reactive Oxygen Species: Double-Edged Weapon in Host Defense and Pathological Inflammation During Infection - Silwal, Prashanta; Kim, Jin Kyung; Kim, Young Jae; Jo, Eun-Kyeong (Frontiers in Immunology, 2020)
Mitochondria are inevitable sources for the generation of mitochondrial reactive oxygen species (mtROS) due to their fundamental roles in respiration. mtROS were reported to be bactericidal weapons with an innate effector function during infection. However, the controlled generation of mtROS is vital for the induction of efficient immune responses because excessive production of mtROS with mitochondrial damage leads to sustained inflammation, resulting in pathological outcomes such as sepsis. Here, we discuss the beneficial and detrimental roles of mtROS in the innate immune system during bacterial, viral, and fungal infections. Recent evidence suggests that several pathogens have evolved multiple strategies to modulate mtROS for their own benefit. We are just beginning to understand the mechanisms by which mtROS generation is regulated and how mtROS affect protective and pathological responses during infection. Several agents/small molecules that prevent the uncontrolled production of mtROS are known to be beneficial in the maintenance of tissue homeostasis during sepsis. mtROS-targeted approaches need to be incorporated into preventive and therapeutic strategies against a variety of infections.